Pd nanoparticles confined in mesoporous N-doped carbon silica supports: a synergistic effect between catalyst and support. Issue 5 (30th January 2020) - Oliveira, Rafael L.; Kerstien, Julius; Schomäcker, Reinhard; Thomas, Arne
Abstract : Palladium nanoparticles of similar size were deposited on different supports, layers of carbon materials (with and without nitrogen doping) on the surface of a MCF (mesocellular foam) silica. Abstract : Palladium nanoparticles of similar size were deposited on different supports, layers of carbon materials (with and without nitrogen doping) on the surface of a MCF (mesocellular foam) silica. For the generation of the N-doped carbon coatings, three different N sources were used to also investigate a possible influence of the N-doped carbon precursor and thus the structure of the N-doped carbons on their performance as catalyst support. These catalysts were tested for the Suzuki coupling and hydrogenation reactions. For the Suzuki reaction, the carbon coatings showed to increase dramatically the stability of the MCF material. Furthermore, when N-doped carbon coatings were applied, strong improvement of the stability of the catalysts was observed due to an enhanced interaction between metal nanoparticles and the support, preventing metal particle growth. In hydrogenation reactions, the presence of the N-doped carbon coating on the silica support increases the adsorption of aromatic compounds causing an enhancement of the catalytic activity of Pd NPs when compared to the non-doped supports.